RUSSIAN REGIONS INVESTMENT AND INNOVATION POTENTIAL - E. B. Lenchuk; G. A. Vlaskin (Модернизация, инновация, развитие, 2018)
Purpose: the main purpose of the article is to study the current state of the investment and innovation process in the regions of Russia. To achieve this goal, the article solved the following problemsthe: to describe measures to ensure a balanced innovative growth of Russian regions; to substantiate the need for large-scale increase and effective use of investment funds to stimulate the transition to a new quality of economic growth based on the deployment of innovative processes; to investigate the problems of development of large and small business in the regions, as sources of innovation and job creation; to carry out an analysis the cluster approach as the most priority area with great potential for creating new competitive advantages of the regional economy; to evaluate the effectiveness of management tools that have a direct impact on the innovation space in the regions.Methods: the study was conducted using systematic, logical, comparative analysis, grouping and generalization methods, which made it possible to ensure the validity of the results and conclusions of the study.Results: the factors influencing on the investment and innovation development of the regions have been identified, the management tasks solved in interaction at the level of the state, the region and the industrial complex have been identified. These factors allow multiplying and effectively using the opportunities for large and small business in order to modernize, provide the necessary investment support for the innovative development of regions and the country. Using these approaches give the opportunity to increase the effectiveness and quality of the influence of these factors and tasks on the innovative development of the regions and to adapt their strategy of innovative modernization.Conclusions and relevance: the article show the special role of active investment-innovative interaction between the national and regional levels of public administration for implementation of modernization processes in the economy in order to build a common innovation space in the whole country.